The Study on Zakat Collection Through Social Media Marketing: The Case of Johor - Muhammad Suhaimi Sulong,; Mustapahayuddin Abdul Khalim,; Mohd Shafie Mustapha,; Nur Zainatul Nadra Zainol,; Ahmad Zaki Mohamad Malom,; Wan Ainaa Mardhiah Wan Zahari, (Journal of Social Transformation and Regional Development, 2024)
Zakat is a religious practice where Muslims donate part of their wealth to those in need. It is a mandatory responsibility imposed on financially capable Muslims as outlined in the five pillars of Islam. As Allah SWT said in Surah At-Tawbah Verse 103: “Take, [O Mu?ammad], from their wealth a charity by which you purify them and cause them to increase, and invoke [All?h's blessings] upon them. Indeed, your invocations are reassurance for them. And All?h is Hearing and Knowing.” [9:103]. Thus, this study highlights the Johor Islamic Religious Council (MAINJ) in providing information and awareness on zakat to the general public by continuing the use of social media marketing as a reliable strategy for zakat collection activities. MAINJ is currently making announcements and promotions on Zakat through its official Facebook, Instagram, YouTube, and TikTok channels. During the COVID-19 pandemic lockdown in 2020 and 2021, there has been an increase in zakat collection among Muslims in Johor and shown the highest collection for the past five years. This statistically shows that the Muslim community has a high awareness of paying zakat. Social media channels provided by MAIJ have been able to provide accurate input and information about Zakat while also providing opportunities to pay Zakat online. In the future, the Twitter platform will be considerably used by MAINJ to expand their prospects in the Zakat collection among corporate agencies and the younger generation.